Palliative care research promotion in policy and practice: a knowledge exchange process. Issue Volume 12:Issue e3(2022) (16th August 2021) - Finucane, Anne; Carduff, Emma; Meade, Richard; Doyle, Sarah; Fenning, Stephen; Cumming, Stuart; Hekerem, Diana; Rahman, Fariel; Lugton, Jean; Johnston, Bridget; Murray, Scott A
Abstract : In palliative care, as in many areas of medicine, there is a considerable amount of research conducted that makes sound recommendations but does not result consistently in improved care. For instance, though palliative care has been shown to benefit all people with a life-threatening illness, its main reach continues to be for those with cancer. Drawing on relational models of research use, we set out to engage policy-makers, educators, clinicians, commissioners and service providers in a knowledge exchange process to identify implications of research for Scottish palliative care priorities. First, we mapped the existing palliative care research evidence in Scotland. We then organised evidence review meetings and a wider stakeholder event where research producers and users came together to coproduce implications of the evidence for policy, education and practice. We used questionnaires and key stakeholder feedback meetings to explore impacts of this process on research uptake and use immediately after the events and over time. In this paper, we reflect on this knowledge exchange process and the broader context in which it was set. We found that participation fostered relationships and led to a rich and enthusiastic exploration of research evidence from multiple perspectives. Potential impacts relating to earlier identification for palliative care, education and need-based commissioning ensued. We make suggestions to guide replication.